2013
DOI: 10.1267/ahc.13036
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Administration of Recombinant Human Keratinocyte Growth Factor Promotes Alveolar Epithelial Cell Proliferation during Compensatory Lung Growth in Rat

Abstract: Keratinocyte growth factor (KGF) is considered to be one of the most important mitogens for lung epithelial cells. The objectives of this study were to confirm the effectiveness of intratracheal injection of recombinant human KGF (rhKGF) during compensatory lung growth and to optimize the instillation protocol. Here, trilobectomy in adult rat was performed, followed by intratracheal rhKGF instillation with low (0.4 mg/kg) and high (4 mg/kg) doses at various time-points. The proliferation of alveolar cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Villus height, crypt depth, intestinal wet weight, RNA levels and protein expression analysis also indicated that AhR knockout mice presented compromised KGF-induced intestinal changes. Previous studies have reported that AhR, as a conserved nuclear transcription protein, serves an important role in cell proliferation ( 24 27 ). Interestingly, other work in the field found that AhR regulates the expression of receptors that meditated cell survival and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Villus height, crypt depth, intestinal wet weight, RNA levels and protein expression analysis also indicated that AhR knockout mice presented compromised KGF-induced intestinal changes. Previous studies have reported that AhR, as a conserved nuclear transcription protein, serves an important role in cell proliferation ( 24 27 ). Interestingly, other work in the field found that AhR regulates the expression of receptors that meditated cell survival and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim et al reported that intra-tracheal multicycle application of 10 mg KGF protein/kg body weight was necessary to achieve a maximal proliferative response in alveolar type II epithelial cells in the elastase-induced emphysema model [ 46 ]. On the other hand, Furukawa et al reported that the repeated administration of a low dose of KGF (0.4 mg/kg) gave the same effect as that of administration of a high dose (4 mg/kg) [ 12 ]. Currently, the optimal treatment threshold for the gene transfer method using electroporation in this animal model is unclear, because of differences in the route of administration and the absorption efficiency in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…We also previously showed that administration of a KGF-expressing plasmid using electroporation significantly enhanced compensatory lung growth [ 24 ]. Moreover, exogenous KGF was shown to augment lung epithelial cell proliferation and to decrease the average airspace distance [ 12 ]. In terms of COPD treatment , we therefore considered that KGF, which is synthesized in different tissues far from the lung, may play a beneficial role in lung repair or preventing progression of emphysema.…”
Section: Introductionmentioning
confidence: 99%